2009
DOI: 10.1017/s1743921311002201
|View full text |Cite
|
Sign up to set email alerts
|

Orientations of dolmens in Western Europe

Abstract: Abstract. The communal tombs ('dolmens') constructed through Europe and the Mediterranean region in the late Neolithic nearly always had an entrance to permit the introduction of further bodies, and hence an orientation. Extensive fieldwork shows that the builders always felt constrained to observe a custom of orientation, and in most of Western Europe the custom may well have been to face the rising Sun at some time of year, or the Sun after it had risen. But at Fontvieille near Arles the local custom was qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…The x 2 -test showed that the majority of the spokes of the wheels in that cluster are oriented for some reason to stretch in a SEeNW direction. This bearing points at the quartile of the horizon where the sun rises during the winter solstice; that is the dominant orientation of the funerary megalithic structures of the Mediterranean (Hoskin, 2009). Whether this alignment was indeed intended by the prehistoric builders, or owes to a local topographical peculiarity, that can not be identified at the current observation scale, can not be answered at the moment.…”
Section: Discussionmentioning
confidence: 84%
“…The x 2 -test showed that the majority of the spokes of the wheels in that cluster are oriented for some reason to stretch in a SEeNW direction. This bearing points at the quartile of the horizon where the sun rises during the winter solstice; that is the dominant orientation of the funerary megalithic structures of the Mediterranean (Hoskin, 2009). Whether this alignment was indeed intended by the prehistoric builders, or owes to a local topographical peculiarity, that can not be identified at the current observation scale, can not be answered at the moment.…”
Section: Discussionmentioning
confidence: 84%
“…The orientations of the aggregated data set (n = 144) is only slightly significant (p = 0.04). As a point of comparison, Neolithic communal tombs often face the midsummer sunrise (Hoskin 2008) and Neolithic long houses are sometimes oriented to the geographic area of that community's origins (Bradley 2001). The recognisable doorways are commonly positioned perpendicular to the long axis, although only 37% of the rings have definite openings.…”
Section: Resultsmentioning
confidence: 99%
“…The study of prehistoric astronomy in the British Isles and northwest Europe, as well as in other regions, has been primarily based on the assumption that the ancient peoples were interested in celestial bodies as they rose and set along the horizon (Burl 1993(Burl , 2000Criado-Boado and Villoch-Vázquez 2000;Dowd and Milbrath 2015;González-García and Belmonte 2014;Heggie 1981;Patrick and Freeman 1985;Ruggles et al 1991;Scarre 2005;Mörner 2012Mörner , 2015Ruzicka 2015;Šprajc and Sánchez Nava 2015;Thom 1978, 1980;Hoskin 2009). Much of the study done by archaeologists and others on astronomy in prehistory therefore specifically focuses upon this connection.…”
Section: Astronomy In Prehistoric Western Scotland: Previous Technicamentioning
confidence: 99%